Relationship between the qualification and labour market situation of disabled workers in Hungary - Nagymáté, Nóra (Applied Studies in Agribusiness and Commerce, 2012)
My PhD research focuses on special rehabilitation firms (they are specialised to employ disabled people) and their employees. Two questionnaires for the above mentioned firms and their employees were created in order to gather information on their activities as well as to explore the relationship between the firms and their employees. Altogether 1030 employees and 109 employers filled in the questionnaires. The current study shows the results of this survey. It can be stated that this paper shows the risk of finding a workplace after a certain time period. According to the latest trends I analyse the labour market situation of people living with disabilities with survival analysis. The survival analysis is able to manage partial information, as well. After summarizing all claims of participants we can make an impression in this area and demonstrate the problems for the labour market generally. I use the Log-rank, Breslow and Tahane-Ware probe.